KEDUDUKAN MAHAR DALAM TAJDI - Hamiliani, Maya; Syarifuddin, Syarifuddin; Norhadi, Muhammad; Hamliani, Maya (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2025)
This research is motivated by the differences in the position of dowry in tajdiddun nikah. that occurs in society. In this case, the head of the religious affairs office (KUA) gave several oponions regarding the position of the dowry in the tajdiddun nikah. Therefore, the focus of this research is on the position of dowry in tajdiddun nikah and what arguments are used by the marriage officer regarding the legal position of dowry in tajdiddun nikah in Palangka Raya City. The qualitative method used in this research uses empirical legal research with a sociological juridical type with a socio-legal approach. The results of the research show: 1. There are 4 opinions regarding the position of Mahar in tajdiddun nikah. First, requiring a new dowry at the in tajdiddun nikah on the grounds that the previous dowry was the wife's right and most likely the wife had already used the dowry. Second, the dowry in in tajdiddun nikah uses the old dowry, because in tajdiddun nikah does not cancel the first marriage. Third, the determination of the dowry depends on the condition of the tajdiddun nikah, if the tajdiddun nikah is only for KUA administration or the previous marriage is not invalidated then there is no need to use a new dowry, you can use the dowry from the first marriage. However, if the tajdiddun nikah is due to the words talak being spoken and the iddah period has been completed then it is obligatory to use a new dowry. Fourth, the determination of the dowry is based on the agreement of both parties, meaning that the amount or level of the dowry is determined by the husband and wife who wish to carry out in tajdiddun nikah, may use the old dowry or use the new dowry. 2. Among the arguments given by the marriage officer is that the harmony and conditions of marriage must be fulfilled, then based on the al-quran and the hadith of Rasulullah, KHI, the opinion of Imam Hajar Al-Haitami and the opinion of Imam Yusuf Al-Ardabili.